Quasi‐real‐time photon pulse duration measurement by analysis of FEL radiation spectra. (1st January 2016) - Engel, Robin; Düsterer, Stefan; Brenner, Günter; Teubner, Ulrich
Abstract : For photon diagnostics at free‐electron lasers (FELs), the determination of the photon pulse duration is an important challenge and a complex task. This is especially true for SASE FELs with strongly fluctuating pulse parameters. However, most techniques require an extensive experimental setup, data acquisition and evaluation time, limiting the usability in all‐day operation. In contrast, the presented work uses an existing approach based on the analysis of statistical properties of measured SASE FEL spectra and implements it as a software tool, integrated in FLASH's data acquisition system. This allows the calculation of the average pulse durations from a set of measured spectral distributions with only seconds of delay, whenever high‐resolution spectra are recorded.